Segmentation Map, Consumer Preference, and Price Determination Appropriate for Wedding Organizer Business in Jakarta - Melati, Ina; Budiwan, Teddy Indira; Puspokusumo, R.A. Aryanti Wardaya (Journal the Winners: Economics, Business, Management, and Information System Journal, 2018)
This research was aimed to validate segmentation from previous research, determining consumer preference and pricing perception based on preferences selected by the Wedding Organizer (WO) consumer in each validated segment to reach consumer satisfaction. This research was a quantitative descriptive research by using probability sampling with 100 total respondents. The used analytical models, were differences in accordance to each problem studied, those were; (1) segmentation was analyzed by cluster analysis and cross tabulation and, (2) consumer preference, as well as pricing perception, were analyzed by cross tabulation. This research produces three segmentations of wedding organizer users and their appropriate product and service preference, including price perception from each of the consumers. In terms of fair price, each segment has their own perception. Smart couple prefers standard portfolio in product and office performance, employee quality and service contract in service, priced in 65 Mio – 125 Mio. Uncle Scrooge prefer catering, rundown management and makeup & wardrobe in product and employee quality in service, all in the price range of 65 Mio – 125 Mio. Familiar face couple has catering in product preference and consultant allocation in service preference, all in the price range of 65 Mio – 125 Mio.